Identifying and responding to family adversity in Australian community and primary health settings: a multi-site cross sectional study - Hall, Teresa; Constable, Leanne; Loveday, Sarah; Honisett, Suzy; Schreurs, Natalie; Goldfeld, Sharon; Loftus, Hayley; Jones, Renee; Reupert, Andrea; Yap, Marie B. H.; Woolfenden, Sue; Montgomery, Alicia; et al. (Frontiers in Public Health, 2023)
Background: Unaddressed family adversity has potentially modifiable, negative biopsychosocial impacts across the life course. Little is known about how Australian health and social practitioners identify and respond to family adversity in community and primary health settings.Objective: To describe, in two Australian community health services: 1) the number of adversities experienced by caregivers, 2) practitioner identification of caregivers experiencing adversity, 3) practitioner response to caregivers experiencing adversity, and 4) caregiver uptake of referrals Methods: Survey of caregivers of children aged 0-8 years attending community health services in Victoria and New South Wales (NSW). Analysis described frequencies of caregiver self-reported: 1) experiences of adversity, 2) practitioner identification of adversity, 3) practitioner response to adversity, and 4) referral uptake. Analyses were sub-grouped by three adversity domains and site.Results: 349 caregivers (Victoria: n=234; NSW: n=115) completed the survey of whom 88% reported experiencing one or more family adversities. The median number of adversities was 4 (2-6). Only 43% of participants were directly asked about or discussed an adversity with a practitioner in the previous six months (Victoria: 30%; NSW: 68%). Among caregivers experiencing adversity, 30% received direct support (Victoria: 23%; NSW: 43%), and 14% received a referral (Victoria: 10%; NSW: 22%) for at least one adversity. Overall, 74% of caregivers accepted referrals when extended.The needs of Australian families experiencing high rates of adversity are not systematically identified nor responded to in community health services. This leaves significant scope for reform and enhancement of service responses to families experiencing adversity.